Improve Religious Life Experience In The Concept Of Spiritual Causes Through Beneran Indonesia - Muhammad Mona Adha; Eska Prawisudawati Ulpa; Agustinus Tampubolon; Erwin Susanto; Edi Siswanto (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2022)
Abstract: Realizing social happiness and harmony in inter-religious relations from a broad perspective. Every religious human being always learns to gain solemnity and understanding in the religious life that is carried out. This article explores qualitative research using an ethnographic approach in one activity space with a homogeneous component of respondents. The aim of the research is to find the relationship of solidarity and synergy among young people of different religions in Beneran Indonesia's volunteer activities. The research respondents were the founders of the Beneran Indonesia Foundation and the participating volunteers. Data and information were collected from observations, interview results, and supporting documents which were then analyzed and interpreted using the available data. The results of the study show that spiritual causality (reciprocity of an activity) is supported by openness of individual attitudes, responsibility, willingness to work together in developing inter-religious harmony facilitated by meeting rooms or meetings of young people, so that each individual has an answer. causality in the values of life. The participation of students and volunteers in the Beneran Indonesia program is the essence of encounters from different religious, cultural and habitual backgrounds, so that the values of self-perception and individual self-position can be seen and at the same time provide answers for oneself to behave and interact to strengthen social order. community harmony. Positive causality is demonstrated by activities, communication, solidarity, and tolerance raised by volunteers and participants who take part in Beneran Indonesia activities.Keywords: Experience, Religious, Spiritual causality, Young peopleÂ Abstrak: Mewujudkan kebahagiaan dan keharmonisan sosial masyarakat dalam hubungan antar umat beragama dilihat dari perspektif yang luas. Setiap manusia umat beragama selalu belajar untuk mendapatkan kekhidmatan dan pemahaman dalam hidup keagamaan yang dijalankan. Artikel ini dieksplorasi dari penelitian secara kualitatif dengan pendekatan etnografi dalam satu ruang kegiatan dengan komponen responden yang homogen. Tujuan penelitian adalah untuk menemukan hubungan solidaritas dan sinergi anak-anak muda yang berbeda agama dalam aktivitas volunteer Beneran Indonesia. Responden penelitian adalah pendiri Yayasan Beneran Indonesia dan para volunteer yang berpartisipasi. Data dan informasi dikumpulkan dari observasi, hasil wawancara, dan dokumen pendukung yang kemudian dianalisis dan diinterpretasikan dengan data yang tersedia. Hasil penelitian menunjukkan bahwa kasusalitas (hubungan timbal balik dari sebuah aktivitas) spiritual didukung oleh keterbukaan sikap individu, bertanggung jawab, mau bekerja sama dalam mengembangkan kerukunan antar umat beragama dengan difasilitasi ruang bertemu atau pertemuan anak-anak muda, sehingga setiap diri individu mempunyai jawaban atas kausalitas dalam nilai-nilai kehidupan. Partisipasi siswa dan volunteer dalam program Beneran Indonesia merupakan esensi perjumpaan dari latar belakang agama, budaya, dan kebiasaan yang berbeda-beda, sehingga nilai persepsi diri dan posisi diri individu dapat terlihat dan sekaligus memberikan jawaban terhadap diri sendiri untuk berperilaku dan berinteraksi untuk memperkuat tatanan sosial harmoni masyarakat. Kausalitas secara positif ditunjukkan dengan aktivitas, komunikasi, solidaritas, serta toleransi yang dimunculkan oleh volunteer dan peserta yang ikut serta dalam kegiatan Beneran Indonesia.Kata kunci: Anak-anak muda, Kausalitas spiritual, Keagamaan, Pengalaman